Causes of changing stock of the Amur pike Esox reichertii - Elena V. Ostrovskaya (Известия ТИНРО, 2017)
Retrospective data on catches of fine-mesh fishes in the Amur collected by Khabarovsk branch of the Pacific Fish. Res. Center (TINRO) since 1937 are analyzed. The main factors influencing on stock and catches of the Amur pike Esox reichertii (Dybowski, 1869) are revealed by methods of multiple regression and variance analyses, as the water level and preceding withdrawal by fishery. Dependence of the pike annual catch on these factors in preceding year (annual landing and the water level in June-September) and in current year (the water level in June) describes about 80 % of the catches variation. The tendency to both stock and landings decreasing since in the late 20th century is caused by the Amur water regime change. Ways of the stock recovery in conditions of low water level are discussed.